Practical urologic cytopathology - Bardales, Ricardo H. (Oxford University Press, 2002)
Practical Urologic Cytopathology presents the state-of-the-art diagnosis of disorders of the urinary tract. Illustrated with almost 300 full color photomicrographs, the text highlights the "key concepts" of each disorder. Recent and classic concepts are combined, especially with regard to the classification of urothelial tumors.